The first longhorned beetle record for the Prepuna in the Bolivian Andes and Potosi Department in Bolivia: a new species of Dirocoremia (Coleoptera: Cerambycidae: Rhopalophorini) - Perger, Robert; Guerra, Fernando (Zootaxa, 2015)
Compared to other Bolivian ecoregions, the Prepuna and Puna in the Bolivian highlands are distinguished by low precipitation and low biological diversity. These factors have likely contributed to the perception that the Prepuna and Puna are less interesting for entomological studies, and reports of longhorned beetles from these regions remain scarce. Here, the first longhorned beetle record for the Bolivian Prepuna and Potosi Department is reported, an unknown species of Dirocoremia Marques, 1994. Dirocoremia tupizai sp. n. can be distinguished from congeners by its dark-brown to black metatibiae with short and sparse subapical brushes of hairs.